Mother's participation in paid work: the role of 'mini-jobs' - Hales, Jon; Tipping, Sarah; Lyon, Nick (London, 2007)
"In late 2005 and early 2006, there was a gap of 15 percentage points in the rate of participation in paid work by mothers, according to whether they lived in a family with a partner or were living as a lone parent. Around half of this gap is a reflection of it being more common for mothers in couple families to work in a job where their hours are between one and 15 per week, referred to as 'mini-jobs'. Previous research into 'mini-jobs' had identified a pattern of working in which mothers moved from not working at all, through a transitional period in a 'mini-job', to working 16 hours or more per week. One of the primary aims of this research was to consider how big a phenomenon is the use of 'mini-jobs' in moving into work of longer hours compared to other routes out of not working.